The Effect of Active Carbon from Coconut Shell as an Adsorbent on Motorcycle Exhaust Gas Emissions and Engine Performance - Mohammad Sukri Bin Mustapa; Agus Setiawan; Gumono Gumono (Asian Journal Science and Engineering, 2023)
This study investigates the advantages of using active carbon as a catalyst, including its deodorizing and color adsorption properties, its ability to act as a purifying agent, common adsorbent, and permeable membrane. Additionally, active carbon exhibits strong binding power to substances that are physically or chemically separated. The objectives of this research are to compare the exhaust gas emissions of motorcycles before and after the application of an adsorbent on the muffler and to analyze the effects of active carbon derived from coconut shell on the engine speed of carbon monoxide (CO), and hydrocarbons (HC). The experimental approach involved conducting laboratory experiments with varying masses of active carbon to collect data. The independent variables were the mass of active carbon and the engine speed, while the dependent variables were the emissions of CO, and HC. The results indicated that using 200 grams of active carbon derived from coconut shell as an adsorbent resulted in a 12.06% decrease in CO emissions, and a 16.96% decrease in HC emissions. Keywords: Active Carbon, Exhaust Gas Emissions, Coconut Shell